Topical Isotretinoin in Acne Vulgaris - Rahman, M Moksedur; Abdullah, M; Hossain, M Moazzem; Siddique, MA; Nessa, M; Rahman, MK; MMR, Khan; Rahman, M Zillur; Taher, SMA; AfzalUddin, SM (TAJ: Journal of Teachers Association, 2018)
This study was carried out to evaluate the efficacy, safety and adverse effects of topical isotretinoin 0.05% gel in the treatment of acne vulgaris. This prospective study was undertaken in Skin & VD outpatient department of Rajshahi Medical College Hospital, Rajshahi. One hundred patients with mild tomoderate acne vulgaris were enrolled and were instructed to apply isotretinoin 0.05% gel once daily at night for 12 weeks. Patients were followed up at 2,4,8 and 12 weeks for efficacy and tolerability. Efficacy was measured by counting facial inflammatory and noninflammatory lesions and by grading acne severity. Cutaneous tolerance was assessed by determining erythema, scaling and burning with pruritus.Response was excellent in 80%of cases.None of the cutaneous reactions was severe, all were mild and well tolerated.Nobody had to discontinue the therapy for side effects. This study confirms that isotretinoin 0.05% gel is safe and effective topical therapy for mild to moderate acnevulgaris. TAJ 2016; 29(2): 1-5